2005
DOI: 10.1080/03079450500059206
|View full text |Cite
|
Sign up to set email alerts
|

In ovoinhibition of fowlpoxvirus replication by a gall extract fromGuiera senegalensis

Abstract: Several field isolates of fowlpoxvirus (FPV) from Burkina Faso, West Africa, were isolated and partly evaluated by molecular analysis. In addition, the in ovo antiviral activity against FPV of a gall extract from Guiera senegalensis was determined. Three viral isolates were obtained from suspected fowlpox cases after passage in embryonating chicken eggs and their poxviral identity confirmed by electron microscopy. All isolates were found to be pathogenic for chicks and all grew well in cell culture. Polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…These active substances, that have medicinal property can be extracted and used in different forms to prevent or treat some diseases (SOFOWORA, 1996). In ovo feeding research has shown that vegetal extracts from plants such as Toussaintia patriciae, Eugenia jambolana and Guiera senegalensis, improved chicken immune status against infectious bursal virus, avian influenza virus (H5N1) and fowl poxvirus (NYANDORO et al, 2014, SOOD et al, 2012, LAMIEN et al, 2005. Moringa oleifera is also another promising tree with a good profile of important trace elements, good sources of proteins, vitamins and can be used as animal feed (ANWAR et al, 2007;DOUGNON et al, 2012;SULTANA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These active substances, that have medicinal property can be extracted and used in different forms to prevent or treat some diseases (SOFOWORA, 1996). In ovo feeding research has shown that vegetal extracts from plants such as Toussaintia patriciae, Eugenia jambolana and Guiera senegalensis, improved chicken immune status against infectious bursal virus, avian influenza virus (H5N1) and fowl poxvirus (NYANDORO et al, 2014, SOOD et al, 2012, LAMIEN et al, 2005. Moringa oleifera is also another promising tree with a good profile of important trace elements, good sources of proteins, vitamins and can be used as animal feed (ANWAR et al, 2007;DOUGNON et al, 2012;SULTANA et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Data were obtained from the macroscopic image of CAM and the number of pock lesions was counted on the CAM of the ECEs in all groups [9,26]. Group VIII, a control for the herbal and herbal toxicity test, was used to determine the maximum non-toxic concentration of each extract concentration [8,9].…”
Section: In Ovo Testmentioning
confidence: 99%
“…Mortality is usually low in birds with a mild cutaneous form of the disease; however, it becomes a significant problem with systemic infection when diphtheric lesions are dominant or when the disease is accompanied by other infections or poor environmental conditions [ 5 - 7 ]. Therapy for avian pox is not available; however, an alternative to control avian pox may lie in the use of medicinal plants [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, methanolic extracts of different Sudanese medicinal plants were observed to exhibit antiviral activity against FWPV [57] as well as aqueous decoctions and acetone extracts of galls of Guiera senegalensis J. F. Gmel. (Combretaceae) in vitro, in ovo, and in vivo [58][59][60]. Treatments with an ethanolic extract of the root bark from Synadenium glaucescens Pax (Euphorbiaceae) demonstrated significantly higher mean embryo weight in an in ovo assay against FWPV compared with other extracts of the same plant [61].…”
Section: Poxviridaementioning
confidence: 99%